2016
DOI: 10.1007/s12403-016-0204-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride in Drinking Water in 31 Provinces of Iran

Abstract: The effects of acute fluoride toxicity have been well documented in the literature. Drinking water is an important source of fluoride intake by humans, hence studies need to be carried out to determine the concentration of Fluoride in water. Therefore, this study tends to demonstrate the fluoride concentration in drinking water in thirty-one provinces of Iran during 2014. This cross-sectional study on drinking water was conducted in 2014. SPADNS method was determined for fluoride concentration examination acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…The thyroid gland is the most sensitive tissue in the body to fluoride [2]. Basha et al (2011) and Dey and Giri (2016) stated that TSH hormone as well as T 3 and T 4 hormones decreased due to excess fluoride concentration and thus cause hypothyroidism in some populations [1,2]. This paper showed this reality that the value of TSH hormone increased by increasing water fluoride concentration.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The thyroid gland is the most sensitive tissue in the body to fluoride [2]. Basha et al (2011) and Dey and Giri (2016) stated that TSH hormone as well as T 3 and T 4 hormones decreased due to excess fluoride concentration and thus cause hypothyroidism in some populations [1,2]. This paper showed this reality that the value of TSH hormone increased by increasing water fluoride concentration.…”
Section: Discussionmentioning
confidence: 80%
“…Yazd city is the driest residential area in Iran [40]. Kheradpisheh et al (2016) found that the mean ± SD of drinking water fluoride is 0.5 mg/L ± 0.27 in this area [3]. This nested case and control study selected cases and controls from Yazd Healthy Study (YaHS) which is a prospective cohort study.…”
Section: Study Area Sample Size Hormones Analyzementioning
confidence: 99%
See 2 more Smart Citations
“…It has a three to four time’s higher probability of occurring in women than in men 6 . The adverse effects of fluoride on animal and human health are well documented in the literature 7 , 8 . The effects of high fluoride ingestion through drinking water, green tea, and ambient air pollution on thyroid hormones (T3, T4, TH, and TSH) were investigated in both humans and animals.…”
Section: Introductionmentioning
confidence: 99%